KEBIJAKAN DIVIDEN DAN SIKLUS HIDUP PERUSAHAAN: Studi Pada Perusahaan Manufaktur - Salvatori, Etheldreda Gladys; Robiyanto, Robiyanto (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2020)
The purpose of this research is to know the influence of RETE, CASHTA, TETA, ROE, SIZE, LEVERAGE on the dividend policy on the company lifecycle of 2014-2018 listed on the Indonesia Stock Exchange (IDX). The population of this research was an IDX registered manufacturing company in 2014-2018, with a total population of 170 companies. The sampling technique used in this research is purposive sampling, and 76 companies were obfained. The independent variables of this research are RETE, CASHTA, TETA, ROE, SIZE, LEVERAGE; While the dependent variable of this research is a dividend policy. The results of this research show that RETE, CASHTA, TETA, SIZE, LEVERAGE are not significant to the dividend policy on the company's lifecycle. In general, there is a variable ROE that has a significant influence on the dividend policy. Further, if analysis is conducted on each company's lifecycle, the ROE has a significant effect on the dividend policy at the start-up stage.